Multifaceted Role of the Urokinase-Type Plasminogen Activator (uPA) and Its Receptor (uPAR): Diagnostic, Prognostic, and Therapeutic Applications - Mahmood, Niaz; Mihalcioiu, Catalin; Rabbani, Shafaat A. (Frontiers in Oncology, 2018)
The plasminogen activator (PA) system is an extracellular proteolytic enzyme system associated with various physiological and pathophysiological processes. A large body of evidence support that among the various components of the PA system, urokinase-type plasminogen activator (uPA), its receptor (uPAR) and PA inhibitors 1 and 2 (PAI-1, PAI-2) play a major role in tumor progression and metastasis. The binding of uPA with uPAR is instrumental for the activation of plasminogen to plasmin which in turn initiates a series of proteolytic cascade to degrade the components of the extracellular matrix, and thereby, cause tumor cell migration from the primary site of origin to a distant secondary organ. The components of the PA system show altered expression patterns in several common malignancies which have identified them as ideal diagnostic, prognostic, and therapeutic targets to reduce cancer-associated morbidity and mortality. This review summarizes the various components of the PA system and focuses on the role of uPA-uPAR in different biological processes especially in the context of malignancy. We also discuss the current state of knowledge of uPA-uPAR targeted diagnostic and therapeutic strategies for various malignancies.